2013
DOI: 10.1128/jb.00437-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions of VirB11 Traffic ATPases with VirB4 and VirD4 Molecular Motors in Type IV Secretion Systems

Abstract: Pilus biogenesis and substrate transport by type IV secretion systems require energy, which is provided by three molecular motors localized at the base of the secretion channel. One of these motors, VirB11, belongs to the superfamily of traffic ATPases, which includes members of the type II secretion system and the type IV pilus and archaeal flagellar assembly apparatus. Here, we report the functional interactions between TrwD, the VirB11 homolog of the conjugative plasmid R388, and TrwK and TrwB, the motors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 39 publications
3
55
0
2
Order By: Relevance
“…To fulfill their coupling functions, T4CPs must interact with secretion substrates and cognate T4SS channels. The latter contacts were not a major focus of our study, but prior work has shown that T4CPs interact with VirB10-like subunits, as well as the VirB4-and VirB11-like ATPases (15,18,30,44,47,82). This interaction network is required not only for early-stage reactions mediating substrate transfer across the inner membrane but also for transduction of intracellular signals across the T4SS channel, enabling substrate translocation to the cell exterior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To fulfill their coupling functions, T4CPs must interact with secretion substrates and cognate T4SS channels. The latter contacts were not a major focus of our study, but prior work has shown that T4CPs interact with VirB10-like subunits, as well as the VirB4-and VirB11-like ATPases (15,18,30,44,47,82). This interaction network is required not only for early-stage reactions mediating substrate transfer across the inner membrane but also for transduction of intracellular signals across the T4SS channel, enabling substrate translocation to the cell exterior.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these or other T4SS ATPase interactions is not fully defined but is predicted to involve contacts between their cytoplasmic domains (37,82,87,88). Accordingly, the VirD4 moieties of the chimeric T4CPs must productively engage with the pKM101-encoded VirB4-like TraB and VirB11-like TraG ATPases for protein transfer through the pKM101 channel.…”
Section: Discussionmentioning
confidence: 99%
“…VirD4 and VirB4, though expected to form hexamers, have been identified in monomeric and dimeric forms as well (Gomis‐Ruth et al , 2001; Schroder et al , 2002; Rabel et al , 2003; Arechaga et al , 2008; Mihajlovic et al , 2009; Durand et al , 2011; Pena et al , 2012; Wallden et al , 2012). All three ATPases interact with one another and these interactions likely direct the two processes in which T4S systems are involved: pilus biogenesis and substrate secretion (Atmakuri et al , 2004; Ripoll‐Rozada et al , 2013). VirD4 also interacts with the N‐terminally located transmembrane helices of VirB10 (Llosa et al , 2003; Ripoll‐Rozada et al , 2013; Segura et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…All three ATPases interact with one another and these interactions likely direct the two processes in which T4S systems are involved: pilus biogenesis and substrate secretion (Atmakuri et al , 2004; Ripoll‐Rozada et al , 2013). VirD4 also interacts with the N‐terminally located transmembrane helices of VirB10 (Llosa et al , 2003; Ripoll‐Rozada et al , 2013; Segura et al , 2013). Although the general organization of the conjugative T4S system is well known, the details of the substrate secretion mechanism are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A second ATPase, VirB11, was shown to be important for pilus assembly 112 , but no VirB11 homologue has been identified for the F-plasmid-encoded T4SS so far 113 . Therefore, the assembly of the F pilus might be powered solely by the activity of the F system's VirB4 homologue, with the help of some other T4SS IMC components.…”
mentioning
confidence: 99%